2021
DOI: 10.1111/1467-9566.13409
|View full text |Cite
|
Sign up to set email alerts
|

A ‘patient–industry complex’? Investigating the financial dependency of UK patient organisations on drug company funding

Abstract: We examined the minimum extent of dependency of UK patient organisations on pharmaceutical industry funding using drug company disclosure reports and patient organisation financial accounts from 2012 to 2016. We used linear regression to explain the overall share of industry funding (‘general dependency’) and top donor funding (‘company‐specific dependency’) in organisations’ income. Predictors included patient organisations’ goal; having members and volunteers; geographical scope of activity; headquarter loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Importantly, the suspicion of absent reports from some companies in Norway and Finland was associated with the lack of a centralized disclosure platform, consistent with the similar experience in the United Kingdom. 4,25,26 For example, 24 pharmaceutical companies, almost 40% of the total number, mentioned by UK patient organizations as donors in 2012–2016 did not disclose any payments. 26 From the perspective of transparency, it is therefore helpful that Norwegian and Finnish PTAs have set up gateways that should allow access to companies’ disclosure websites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, the suspicion of absent reports from some companies in Norway and Finland was associated with the lack of a centralized disclosure platform, consistent with the similar experience in the United Kingdom. 4,25,26 For example, 24 pharmaceutical companies, almost 40% of the total number, mentioned by UK patient organizations as donors in 2012–2016 did not disclose any payments. 26 From the perspective of transparency, it is therefore helpful that Norwegian and Finnish PTAs have set up gateways that should allow access to companies’ disclosure websites.…”
Section: Discussionmentioning
confidence: 99%
“…1 These collaborations often involve companies providing patient organizations with funding, 2 which is likely to increase their capacity. 3 At the same time, industry funding may shape patient organizations’ agendas and ideologies 2,4 —for example, prompting some industry-funded organizations to lobby governments for expanded access to novel drugs, 5–9 rather than to lobby industry to lower drug prices to achieve the same goal. 10,11 Furthermore, industry sponsorship may weaken patient organizations’ representativeness and credibility 12,13 and influence which organizations, voices, and diseases get more attention in society.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“… 17 Most recently, a UK study found headquarter distance from country capitals predicts patient organisations’ dependence on pharmaceutical company funding. 53 To date, research has not considered the locations of patient and healthcare organisations as the reporting requirements do not extend to disclosing country locations. 17 25 28 …”
Section: Introductionmentioning
confidence: 99%